PASAR RAKYAT NATUNA - Uul Pizzi Noviargi; Irwin Irwin; Yudi Purnomo (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
The market is a place where buyers and sellers meet to conduct buying and selling transactions of goods and services. The characteristic of a market is the existence of transaction or buying and selling activities. The market has at least three main functions, namely distribution function, price formation function, and promotion function. Natuna is an area where one of the sources of the regional economy relies on natural resources and tourism sector. Natuna supports an important role in both trade and service activities. Along with the development of trade and services activities in Natuna Regency, the development of facilities and infrastructure that support trade and services activities. The role of the market is very important for the Natuna community to make it easier for people to obtain the goods and services needed so that people in Natuna no longer go outside the island or out of town just to shop for clothes and basic daily necessities. The purpose of the design of Natuna People's Market is to produce the design of the people's market in Natuna Regency as a shopping center and trade center. The application of passive cooling in the design of Natuna People's Market is one of the objectives to solve design problems that serve to provide thermal comfort by maximizing natural delivery. The attraction of Natuna People's Market building is from the dynamic form of buildings following the concept of the roof shape of the traditional house in Riau Islands. Another application is in the secondary skin of the building in the form of mats using brown iron plate material to create a color that looks classic and neutral.